1980
DOI: 10.1084/jem.152.3.736
|View full text |Cite
|
Sign up to set email alerts
|

Cellular basis of graft versus host tolerance in chimeras prepared with total lymphoid irradiation.

Abstract: BALB/c mice given allogeneic (C57BL/Ka) bone marrow cells after toal lymphoid irradiation become stable chimeras approximately 80% donor-type and 20% host-type cells in the spleen. The chimeras doe not develop graft vs. host disease (GVHD). Purified cells of C57BL/Ka origin from the chimeras mediated GVHD in lightly irradiated C3H (third party), but not in BALB/c (host-strain) mice. Thus graft vs. host tolerance in the chimeras could not be explained by complete immunodeficiency of donor-type cells, serum bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Spleen cells from both adult mice given TLI (11) and newborn mice (12,13) contain nonspecific suppressor cells of the mixed leukocyte reaction (MLR) before marrow transplantation. Recent evidence suggests that after transplantation of allogeneic or semiallogeneic lymphoid cells, both TLI-treated adult mice (14,15) and newborn mice (16) or rats (17)(18)(19)(20)(21)(22) develop suppressor cells of transplantation immunity which are specific for the tolerizing tissue antigens.…”
mentioning
confidence: 99%
“…Spleen cells from both adult mice given TLI (11) and newborn mice (12,13) contain nonspecific suppressor cells of the mixed leukocyte reaction (MLR) before marrow transplantation. Recent evidence suggests that after transplantation of allogeneic or semiallogeneic lymphoid cells, both TLI-treated adult mice (14,15) and newborn mice (16) or rats (17)(18)(19)(20)(21)(22) develop suppressor cells of transplantation immunity which are specific for the tolerizing tissue antigens.…”
mentioning
confidence: 99%
“…We have previously demonstrated that the donor cell tolerance achieved in C57BL/6-BALB/c stable chimeras is specific to host alloantigens. 17,18 BALB/c mice given allogeneic (C57BL/6) bone marrow cells after lymphoid irradiation become stable chimeras with approximately 80% donor-type and 20% host-type cells in the spleen. 17,18 The levels of donor chimerism closely mimicked those in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 BALB/c mice given allogeneic (C57BL/6) bone marrow cells after lymphoid irradiation become stable chimeras with approximately 80% donor-type and 20% host-type cells in the spleen. 17,18 The levels of donor chimerism closely mimicked those in the current study. Purified donor cells of C57BL/6 origin from the chimeras mediated GVHD in irradiated C3H (third party), but not in irradiated BALB/c (host-strain) mice.…”
Section: Discussionmentioning
confidence: 99%